2016
DOI: 10.1590/bjpt-rbf.2014.0176
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and short-term effects of the combination of dry needling and percutaneous TENS on post-needling soreness in patients with chronic myofascial neck pain

Abstract: BackgroundDry needling (DN) and percutaneous electrical nerve stimulation (PENS) are widely used techniques in the treatment of myofascial pain.ObjectiveTo investigate the immediate and short-term effects of the combination of DN and PENS compared to DN alone on the upper trapezius muscle.MethodThis is a 72-hour follow-up single-blinded randomized controlled trial. Sixty-two volunteer patients with chronic myofascial neck pain with active Myofascial Trigger Points (MTrPs) in the upper trapezius muscle were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
64
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 48 publications
8
64
1
5
Order By: Relevance
“…In the current study, no significant difference was observed regarding LCo thickness between the two groups. The smaller thickness of the LCo muscle in women with FHP was consistent with the findings reported by Ishida et al, 6 who measured the CVA and DCF thickness in healthy men. The results indicated that men with smaller CVAs had smaller DCF muscle thickness.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, no significant difference was observed regarding LCo thickness between the two groups. The smaller thickness of the LCo muscle in women with FHP was consistent with the findings reported by Ishida et al, 6 who measured the CVA and DCF thickness in healthy men. The results indicated that men with smaller CVAs had smaller DCF muscle thickness.…”
Section: Discussionsupporting
confidence: 91%
“… 3 This poor posture has been linked to many musculoskeletal disorders such as headache, shoulder pain, neck pain, craniofacial pain, and temporomandibular disorders. 4 , 5 , 6 , 7 Previous studies have demonstrated a correlation between FHP and disability in patients with neck disorders. 8 Increase in the time spent working on a computer in sitting positions has increased the prevalence of this poor posture.…”
Section: Introductionmentioning
confidence: 97%
“…It can have an impact on the individual's physical, social, and psychological well-being, contributing to increasing costs to society and businesses. In addition, with the increasing aging population of medium- and low-income countries, the prevalence of neck pain will grow significantly in the coming decades, 8 requiring knowledge of the risk factors and forms of preventive and/or curative interventions (for example, global postural re-education, segmental stretching, 9 dry needling, and percutaneous electrical nerve stimulation, 10 among others). It is also important to highlight that, in Brazil, population-based studies regarding pain have been frequently related to lumbar or general pain, 11 while neck pain needs further research.…”
Section: Introductionmentioning
confidence: 99%
“…14,[17][18][19][20][21][22] The purpose of this study was to investigate the effect of DN compared with IC on pain intensity and PPT immediately after each treatment session compared with the measurements obtained 48 hours after each treatment session in individuals with MTP in the UT muscle.…”
Section: Introductionmentioning
confidence: 99%